Femtosecond laser-assisted cataract surgery for the white cataract - Chee, Soon-Phaik; Chan, Nicole Shu-Wen; Yang, Younian; Ti, Seng-Ei (British journal of ophthalmology, 2019)
To report the capsulotomy and lens fragmentation outcomes of white cataracts managed with the femtosecond laser (FL). Outcomes of a prospective, observational consecutive case series of white cataracts (June 2012-November 2016) that underwent FL-assisted cataract surgery (FLACS) (Victus, Bausch+Lomb, Munich, Germany) at the Singapore National Eye Centre were audited. patient demographics, type of white cataract, levelness of docking, anterior capsule position following laser, completeness of capsulotomy and fragmentation, best-corrected visual acuity (BCVA) at 1 month, intraoperative complications. capsulotomy integrity, fragmentation capability and BCVA at 1 month. 58 eyes of 54 patients underwent FLACS. White cataract types included dry white (24 eyes), intumescent (28 eyes) and Morgagnian (6 eyes). Docking was level in 22 eyes (38.6%). Following FL, the anterior capsule level dropped in 20 eyes (34.5%). Incomplete capsulotomies occurred in 10 eyes (17.2%). Lens fragmentation attempted in 38 eyes was effective or partially effective in 31 eyes (81.6%). No anterior or posterior capsule tears occurred. LogMAR BCVA at 1 month was 0.073 (SD 0.09). Risk factors for incomplete capsulotomy were Morgagnian cataract and lens thickness (multiple logistic regression, p<0.01 and p=0.03, respectively). The main complication of FLACS in white cataracts was incomplete capsulotomy (17.2%), significantly associated with Morgagnian cataracts and increased lens thickness. Lens fragmentation was effected in four-fifths of white cataracts but should be avoided in Morgagnian cataracts due to possible overlap of the lens fragmentation plan and the anterior capsule.